24 m langer Hybridbus für umweltfreundlichen Stadtverkehr. Ein Jahr Erfahrung mit Doppelgelenk-Hybridbus in Luxemburg. - Schmitz, Martin (Alba, 2010)
24 m lange Hybridbusse eröffnen vielfältige Optionen für den ÖPNV. Das Luxemburger Busunternehmen Voyages Emile Weber hat nun erste positive Erfahrungen mit einem solchen Fahrzeug des Konsortiums Vossloh Kiepe und Carosserie Hess im Luxemburger Stadtverkehr gemacht.

24m-hybrid busses create varied options for the local passenger transport. The Luxemburg bus company Voyages Emile Weber has made positive experiences in the Luxemburg city-traffic using a vehicle of the consortium Vossloh Kiepe and Carosserie Hess. In May 2009, this 24m-double articulated hybrid bus was commissioned as the first innovation project worldwide. Passenger capacities could be increased considerably during the Luxemburg peak traffic and there are already significant advantages in fuel consumption by the use of this double-articulated bus.
24m-hybrid bus for an eco-friendly city-traffic.
Keywords: Verkehr; Stadtverkehr; ÖPNV; Busverkehr; Fahrzeug; Elektroantrieb; Fahrzeugtechnik; Antriebstechnik; Hybridtechnik; Elektromobilität